THE IMPACT OF INTRINSIC MOTIVATION AND EXTRINSIC MOTIVATION ON THE PERFORMANCE EMPLOYEES OF ABC HOSPITAL SURABAYA - ISTANTI, ENNY (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
Abstract: Purpose–This study aims to find and analyze the influence of intrinsic motivation variables on employee performance, extrinsic motivation variables on employee performance, and dominant influences. Design/methodology/approach–Explain the research design, research methodology Findings–The results of data processing show that there are six indicators of intrinsic motivation variables that are valid and reliable, namely activity, challenges at work, responsibility, self-potential ability, ability to learn new things, and achievement. For extrinsic motivation, there are four valid and reliable indicators, namely recognition, work facilities, relationships. Practical implications–The result is that both intrinsic and extrinsic motivation have a significant effect on employee performance, with a positive relationship. The more intrinsic motivation employees have, the better they perform. Management can pay attention to factors such as activities, challenges in work, responsibilities, self-ability, ability to learn, and achievements. Originality/value–This paper is original Keywords: Intrinsic motivation, extrinsic motivation and employee performance